FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN NOCTURIA PADA PENYANDANG DIABETES MELITUS TIPE-2 - Syarifah, Muflihatus; Subardjo, Yovita Puri; Farida, Farida (Jurnal Gizi dan Pangan Soedirman, 2025)
People with Type-2 Diabetes Mellitus have many complaints of nocturia (waking up to urinate at night). Nocturia increases mortality associated with the risk of falling. This study to determine factors associated with nocturia in people with type 2 diabetes. The type of research is an online observational survey with a cross-sectional design. Data characteristics respondents and nocturia were obtained via google forms. Intakes of caffeine, fluids, and fruit, with a questionnaire recall 1x24 h and a diet high in saturated fat, high protein, and vegetables with a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) by telephone interview. Consecutive sampling obtained 71 respondents. Statistical test with chi-square and logistic regression. 36.6% respondents with type-2 diabetes had complaints of nocturia. The majority were <60 years old (83.1%), female (60.56%), and had type-2 diabetes <10 years (70.4%). Patients with high caffeine intake (25.35%), high fluid intake (45.07%), and high fruit intake (30.99%). Dietary pattern with high protein (43.66%), high saturated fat (39.44%), and low vegetable (67.61%). Variable age, caffeine intake, and fluid intake had Odds Ratio 3.1, 2.8, and 2.1 respectively. There is no relationship between the variables studied and nocturia. Factors that tend a risk for nocturia are age, caffeine intake, and fluid intake.